Analisis Pelaksanaan Program Sanitasi Total Berbasis Masyarakat - Sumiati Sumiati; Andi Yusuf; Asrijun Juhanto (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; The challenges faced by Indonesia related to health development, especially in the field of hygiene and sanitation are still very large, so it is necessary to carry out integrated interventions through a community-based total sanitation approach. Aim; determine the influence of predisposing factors consisting of elements of knowledge, attitudes, perceptions in the 5 pillars of STBM. Method; The type of research used is quantitative observational design with a cross sectional study approach to see the effect of STBM triggering. Results; shows that knowledge, attitudes, family support and support from health workers are significantly related to the implementation of STBM. Meanwhile, the number of dependents, working status, income, and water availability in statistical tests are not related to the implementation of STBM. Knowledge, is the variable that most influences the implementation of STBM, with a significant value (sig.=0.000) or p<0.010 and Exp(B)=12,267. Conclusion; respondents' knowledge of the implementation of STBM is the most influential factor in the implementation of STBM. It is hoped that all parties, especially family support and the support of health workers, support and help each other, motivating the community to always maintain sanitation in their environment.